Hope Tree: An Interactive Art Installation to Facilitate the Expression of Hope in a Hospice Setting. (October 2018) - Collins, Andrew; Bhathal, Darpanjot; Field, Tara; Larlee, Randene; Paje, Rachael; Young, Daneen
Background: Individuals confronting a terminal illness can experience intense psychological distress. Previous research has shown that hope can enhance one's ability to acknowledge, accept, and fight a terminal illness. Patients can continue to have hope or be hopeful, even in the face of a terminal illness. Can participation in a creative writing practice improve the expression of hope in a hospice setting? Methods: In this program evaluation, each expressed hope placed on the "Hope Tree" was independently coded by all research team members utilizing inductive content analysis. Overall themes were derived using a constant comparative approach and arranged into overarching themes based on consensus. Results: Eight major themes emerged from the data: "Peace, " "Dreams, " "Total well-being, " "Acknowledgment of loss, " "Relationships, " "Hospice care, " "Spirituality, " and "Dichotomies." Conclusion: The Hope Tree is a creative art project that can be used within a hospice environment to promote hope among family members and the health-care professionals who care for patients.